TGF-β1-induced regulatory T cells - Hadaschik, Eva; Enk, Alexander (Human immunology, 2015)
Besides central tolerance peripheral tolerance is an important mechanism to avoid development of autoimmunity. Naturally occurring thymic-derived regulatory T cells (nTreg) mediate peripheral tolerance by suppressing autoreactive T cells clones having escaped thymic deletional control. This implies that nTreg have therapeutic potential to dampen autoimmune disease. However, one of the main challenges for the therapeutic application of nTreg still remains the scarce amount of nTreg available. Transforming growth factor beta (TGF-β1) plays a critical role in the generation and immunosuppressive function of nTreg thereby contributing to immune homeostasis. TGF-β1 is thought to be essential for the generation and function of nTreg and regulatory T cells with suppressive properties can be induced in vitro by TGF-β1. These so-called TGF-β1-induced regulatory T cells (iTreg) can be induced in vitro from conventional CD4+ T cells by addition of TGF-β1 and this discovery has added new options to use regulatory T cells therapeutically. Here we discuss the generation and in vitro and in vivo functions of murine and human TGF-β1-induced regulatory T cells in light of potential application as treatment for autoimmune diseases including current problems and drawbacks in their therapeutic use.